Influence of preparation designs, restorative composite cements, and preheating on cementation force and cement thickness - Vitoon, Cholada; Senawongse, Pisol; Saikaew, Pipop; Churnjitapirom, Pornkiat (Mahidol Dental Journal, 2025)
Objectives: To evaluate the effects of two ceramic overlay preparation designs and preheating of two restorative composite resins, Clearfil AP-X and Filtek Z250, on cementation force and cement thickness. Materials and Methods:A total of 112 mandibular first molar resin dies for ceramic overlays were prepared, using either a retentive MOD design (n = 56) or a non-retentive anatomical design (n = 56). Overlays were milled from IPS e.max CAD. Specimens were divided into two groups (n = 28) for cementation force and cement thickness measurements. Each group was further subdivided by luting material (Clearfil AP-X or Filtek Z250), used at room temperature or after preheating to 68 °C for 5 minutes using a Calset device. Restorations were mounted perpendicular to the load axis on a universal testing machine. For thickness measurement, a constant vertical load of 50 N was applied, and the resulting cement thickness was measured. Cementation force was recorded as the load required to achieve a 50 μm cement thickness. Data were analyzed using three-way ANOVA followed by Tukey HSD test at a 0.05 significance level. Results: The non-retentive design with preheated Clearfil AP-X demonstrated the lowest cement thickness (49.46 ± 12.92 μm), which was statistically significantly lower than those of the other groups (p<0.05), while other groups showed cement thicknesses ranging from 79 to 97 μm. Cementation forces ranged from 44 N to 74 N. The preheated Clearfil AP-X group, in both retentive (49.73 ± 7.74 N) and non- etentive (44.45 ± 6.92 N) designs, showed significantly lower cementation forces (p<0.05) compared to other groups. Conclusion: Preparation design, composite type, and preheating significantly influenced cementation. The non-retentive design with preheated Clearfil AP-X showed the lowest cement thickness, approaching the 50 μm ISO threshold, and lower cementation force, highlighting the importance of material and preparation design in achieving thin film thickness and efficient seating for indirect restorations.